The aerobic and anaerobic bacteriology of perirectal abscesses. - Brook, I (1997)
The microbiology of perirectal abscesses in 144 patients was studied. Aerobic or facultative bacteria only were isolated in 13 (9%) instances, anaerobic bacteria only were isolated in 27 (19%) instances, and mixed aerobic and anaerobic flora were isolated in 104 (72%) instances. A total of 325 anaerobic and 131 aerobic or facultative isolates were recovered (2.2 anaerobic isolates and 0.9 aerobic isolates per specimen). The predominant anaerobes were as follows: Bacteroides fragilis group (85 isolates), Peptostreptococcus spp. (72 isolates), Prevotella spp. (71 isolates), Fusobacterium spp. (21 isolates), Porphyromonas spp. (20 isolates), and Clostridium spp. (15 isolates). The predominant aerobic and facultative bacteria were as follows: Staphylococcus aureus (34 isolates), Streptococcus spp. (28 isolates), and Escherichia coli (19 isolates). These data illustrate the polymicrobial aerobic and anaerobic microbiology of perirectal abscesses.